2010
DOI: 10.1177/0333102410381142
|View full text |Cite
|
Sign up to set email alerts
|

Occipital nerve stimulation for the treatment of intractable chronic migraine headache: ONSTIM feasibility study

Abstract: Background: Medically intractable chronic migraine (CM) is a disabling illness characterized by headache ≥15 days per month.Methods: A multicenter, randomized, blinded, controlled feasibility study was conducted to obtain preliminary safety and efficacy data on occipital nerve stimulation (ONS) in CM. Eligible subjects received an occipital nerve block, and responders were randomized to adjustable stimulation (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
329
3
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 365 publications
(353 citation statements)
references
References 30 publications
6
329
3
6
Order By: Relevance
“…Percutaneous nerve stimulation was reported effective for the treatment of various headaches since the 90s (12, 13). Occipital nerve stimulation (ONS) was beneficial for chronic migraine in sham-controlled trials, although the global effect size was modest (14,15,16). The combination of percutaneous ONS and supraorbital nerve stimulation (SNS) was claimed to have a better effect, but randomized controlled trials are lacking (17).…”
Section: The Clinical Evidencementioning
confidence: 99%
“…Percutaneous nerve stimulation was reported effective for the treatment of various headaches since the 90s (12, 13). Occipital nerve stimulation (ONS) was beneficial for chronic migraine in sham-controlled trials, although the global effect size was modest (14,15,16). The combination of percutaneous ONS and supraorbital nerve stimulation (SNS) was claimed to have a better effect, but randomized controlled trials are lacking (17).…”
Section: The Clinical Evidencementioning
confidence: 99%
“…3 months each) RCT were performed in CM [79][80][81]. The ONSTIM study (n = 66 patients, [80]) showed a reduction of C50 % in headache frequency or a decrease of three points on the intensity scale in 39 % of patients treated with active ONS during 12 weeks, compared to no improvement in the ''non-effectively'' stimulated or medically treated groups. Unfortunately, ONSTIM was not powered to convincingly demonstrate effectiveness of ONS.…”
Section: Peripheral Neurostimulation (Pns)mentioning
confidence: 99%
“…In this issue, Paemeleire and Bartsch (page 213) discuss occipital nerve stimulation (ONS). There have been two studies of ONS in migraine: ONSTIM 41 and PRISM. 42 Both failed their primary endpoints.…”
Section: Nerve Block and Device-based Strategiesmentioning
confidence: 99%